2021
DOI: 10.1017/jfm.2021.894
|View full text |Cite
|
Sign up to set email alerts
|

Flow past a rotationally oscillating cylinder with an attached flexible filament

Abstract: Experimental studies are conducted on a rotationally oscillating cylinder with an attached flexible filament at a Reynolds number of 150. Parametric studies are carried out to investigate the effect of cylinder forcing parameters and filament stiffness on the resultant wake structure. The diagnostics are flow visualization using the laser-induced fluorescence technique, frequency measurement using a hot film, and characterization of the velocity and vorticity field using planar particle image velocimetry. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…A splitter plate, attached downstream, inhibits the interaction between the separating shear layers, thereby delaying vortex shedding and resulting in a weaker Kármán vortex street in the wake (Sunil et al. 2022). This reduces the fluctuating lift and drag acting on the bluff body.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A splitter plate, attached downstream, inhibits the interaction between the separating shear layers, thereby delaying vortex shedding and resulting in a weaker Kármán vortex street in the wake (Sunil et al. 2022). This reduces the fluctuating lift and drag acting on the bluff body.…”
Section: Introductionmentioning
confidence: 99%
“…2014; Sunil et al. 2022). It is found that a filament, with proper flexibility and length, may bring about more performance benefits in suppressing/weakening the vortex shedding as compared with a rigid splitter plate with the same length (Wu et al.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations